Social prescribing for frequent attenders in primary care: An economic analysis - Lynch, Mary; Jones, Ceri R. (Frontiers in Public Health, 2022)
Background Social prescribing (SP) is a mechanism to link patients with community groups and third sector organizations. It offers a complimentary approach to the traditional medical models to address psychosocial needs of patients more effectively and in turn aims to reduce demand on the NHS. The aim of this study was to explore the economic benefits related to changes in the use of healthcare resources following a social prescribing intervention in four primary care practices in Wales. Methods Quantitative data from routine healthcare usage was collected from the 78 participants pre and post-intervention. The participants were grouped into frequent attenders (FA) (n = 21) and frequent (n = 57) non-attenders (FNA), and a cost analysis was conducted to estimate cost variances based on healthcare unit usage over the length of the pilot intervention. These were then extrapolated forward to identify potential healthcare savings. Results The SP as an intervention generated the largest cost saving for FAs. The cost variance when FAs participated in the intervention shows there is a direct cost saving of £6,113 or £78.37 per participant over the 5 months of the intervention. Conclusions Results suggest there may be a cost saving associated with SP interventions, however caution should be exercised in interpreting the results due to the lack of control group in this study The cost saving were largest for FAs, where the intervention reduced healthcare unit usage as well as actual and inferred impact on associated healthcare costs. This suggests that in practice to generate the maximum cost benefit SP interventions could be targeted at FAs.